# If p/q= (4/9)^(-3)÷(4/9)^(-2), find(p/q)^(-1)÷(q/p)^(-1)

2
by salonibheron144

2016-01-14T17:48:09+05:30

### This Is a Certified Answer

Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
P/q=(4/9)^(-3) ÷ (4/9)^(-2)
p/q=(9/4)^3 ÷ (9/4)^2
p/q=(9/4)
(p/q)^(-1)=4/9
(q/p)^(-1)=9/4
according to question
(p/q)^(-1)÷(q/p)^(-1)=16/36=4/9
thanks for voting for me
ur wlcm
2016-01-14T20:02:55+05:30

### This Is a Certified Answer

Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
Given p/q=(4/9)^-3÷(4/9)^-2
p/q=(9/4)^3÷(9/4)^2
p/q=9/4
q/p=4/9
now we have to find
(p/q)^-1÷(q/p)^-1
=(q/p)^1÷(q/p)^-1
=(q/p)^2
=(4/9)^2
=16/81